Analytical, Numerical, and Experimental Studies of the Working Process in a Pneumatic Abrasive Installation - Vadym Baha; Ján Piteľ; Ivan Pavlenko (Applied Sciences)
The article presents the results of numerical and experimental studies of a working nozzle for jet-abrasive machining of material surfaces. Nozzle designs with variable geometry were investigated. The aim of the study was to identify reserves for increasing the efficiency of the nozzle to ensure the energy efficiency of the jet-abrasive installation for sustainable production in the context of Industry 5.0. The implementation of numerical modeling made it possible to carry out a series of calculations for the considered nozzle designs using an air-abrasive mixture with flow visualization. The technological parameters of jet-abrasive machining were analyzed. A series of numerical and experimental studies were conducted using the principles of Industry 4.0. Two software packages were used for numerical studies. The results of the calculations that were obtained coincided quite well. Overall, the obtained results made it possible to adjust the settings of the pneumo-abrasive unit in order to get the proper roughness of the processed surface, opt for proper working nozzle design, and determine proper pressure and air consumption for the highest unit efficiency. In a series of studies, the authors proposed a mathematical model for determining the values of mass flow rates of the working medium in the nozzle. The analytical coefficients of the developed model have been obtained. In addition, an approach to determining the main parameters of abrasive blasting based on experimental data was developed. The results obtained were verified by comparing them with the results of experimental studies. It was found that to increase the efficiency of the Venturi nozzle, the outlet cross-section of the considered nozzles should be reduced, and the mass flow rate of the dispersed phase should not significantly affect the speed of the grains of sand at the nozzle outlet.